A SUBJECTIVE ASSESSMENT OF THE SHORT-TERM EFFECTS OF ALCOHOL CONSUMPTION. PRELIMINARY STUDIES ON THE POLISH LANGUAGE ADAPTATION OF “THE BIPHASIC ALCOHOL EFFECTS SCALE - DANIEL KOFI ASSAN, ERZUAH DORIS NKUM; ISAAC –DONKOH; ERIC BAAH (International Journal of Multidisciplinary Research and Studies, 2020)
INTRODUCTION The short-term effects of alcohol consumption are experienced as biphasic, reckoning on the stage of its metabolisation. Usually at the start of the consumption, while the amount of alcohol within the blood is increasing, it’s generally perceived as a stimulant and when decreasing as a sedative. Martin et al.’s Biphasic Alcohol Effects Scale (BAES) could be a self-reported measure of short-term effects of drinking. The study aimed to arrange the Polish adaptation of the dimensions to see its reliability and offer a preliminary assessment of validity. MATERIALS AND METHODS The modified Polish adaptation of BAES is now complete as Skala Efektów Pichia Alkoholu (SEPA) (Scale of Alcohol Drinking Effects). To validate SEPA, Poprawa’s Alcohol Use Scale and Polish adaptation of Fromme, Stroot, and Kaplan’s Comprehensive Effects of Alcohol Questionnaire were used. The research was conducted on two independent samples of young adults: N = 331 and N = 222. RESULTS The two-factor structure of SEPA and validity of modifications were confirmed both within the assessment of moderate and high alcohol dosages. The tool’s reliability indicators were excellent. Both subscales of sedative and stimulant effects adequately and significantly correlate with the expected effects of drinking. The results of the subscale of stimulating effects positively correlate with the expectations of positive effects of alcohol and also the results of the subscale of sedative effects – with negative expectations of alcohol. CONCLUSIONS SEPA reliably measures the subjective short-term twofold effects of drinking: positive stimulant and negative sedative.